Risk factors for distal junctional kyphosis after posterior spinal surgery in adolescent idiopathic scoliosis: a meta-analysis - Jia, Ruili; Long, Yubin (Frontiers in Surgery, 2023)
Introduction: Distal junctional kyphosis (DJK) is a serious complication after posterior spinal surgery in the management of adolescent idiopathic scoliosis (AIS).The purpose of our study is to investigate the predictors for DJK in AIS patients.We searched in the English databases of PubMed, Embase, and the Cochrane Library for clinical researches on AIS. To identify the risk factors for DJK, we collected demographic data, such as age, gender, body mass index, and sagittal parameters, including preoperative pelvic tilt (PT), sagittal vertical axis (SVA), lumbar lordosis (LL), thoracic kyphosis (TK), thoracolumbar kyphosis (TLK), distal junctional angle (DJA), lowest instrumented vertebrae (LIV) relative to sagittal stable vertebrae (SSV) and postoperative DJA. Data was analyzed by RevMan (5.3 version) and STATA (12.0 version)..: Finally, six included articles (1240 patients) showed 9 % (98 out of 1240 patients) of patients suffering from DJK. Our findings indicated that preoperative TK [p=0.007, OR=0.35 95%CI (0.10, 0.61)], TLK [p<0.0001, OR=5.99 95%CI (3.33, 8.65)], and postoperative DJA [p=0.002, OR =0.56, 95%CI (0.21, 0.91)] in the DJK group were markedly higher than those in the non-DJK group. Moreover, patients with LIV above SSV [p<0.0001, OR=7.95, 95%CI (4.16, 15.22)] were more likely to develop DJK. No discernible difference was found in age, sex, BMI, preoperative PT, SVA, LL, or DJA between the two groups. Risk factors of DJK 2Conclusions: Regarding the AIS patients, factors such as higher preoperative TK and TLK, higher postoperative DJA, as well as LIV above the SSV, were related to an increased rate of DJK.